Is there sufficient training of health care staff on noise reduction in neonatal intensive care units? A pilot study from neonoise project - Alberto Alves Carvalhais, Carlos (2021)
Evidence indicates that exposure to high levels of noise adversely affects human health, and these effects are dependent upon various factors. In hospitals, there are many sources of noise, and high levels exert an impact on patients and staff, increasing both recovery time and stress, respectively. The goal of this pilot study was to develop, implement, and evaluate the effectiveness of a training program (TP) on noise reduction in a neonatal intensive care unit (NICU) by comparing the noise levels before and after the implementation of the program. In total, 79 health professionals participated in the study. The measurements of sound pressure levels took into account the layout of the unit and locations of the main sources of noise.